The pasteurized Weissella cibaria alleviates sepsis-induced acute lung injury by modulation of intestinal mucus barrier and gut microbiota - Yuanzhe Li; Debin Yang; Huan Zhao; Liping Dou; Qian Chen; Yibing Cheng; Bo Hu; Yu Tang; Yongtao Duan; Caili Guo; Abbas Sakandar; Dong Li (Journal of Translational Medicine)
Abstract Background Dysbiosis of intestinal microecology caused by sepsis plays a crucial role in the onset and progression of sepsis-induced acute lung injury (SALI). As a postbiotic type, inactivated probiotic bacteria can regulate the gut microbiome. Pasteurized bacteria are considered safer than live bacteria in immune dysregulation disorders. Weissella cibaria (W. cibaria) is considered a candidate probiotic with certain beneficial functions. However, whether inactivated W. cibaria can alleviate SALI and the underlying mechanisms remain unclear. This study aimed to investigate whether inactivated W. cibaria can regulate intestinal mucosal barrier function and gut microbiota, thereby improving SALI. Methods Following gavage of pasteurized W. cibaria in septic mice, lung tissue damage and inflammation levels were assessed. Circulating LPS levels and inflammatory cytokine concentrations in the blood were measured. Additionally, colonic tissue inflammation, intestinal mucosal barrier integrity, and alterations in the gut microbiota were evaluated. Result Pasteurized W. cibaria increases survival rates in SALI mice and improves pathological damage and cell apoptosis in lung tissue. Pasteurized W. cibaria also reduces the lung inflammatory response in septic mice by lowering pro-inflammatory cytokine levels and increasing anti-inflammatory cytokine levels. Pasteurized W. cibaria appears to exert its effects by improving the intestinal mucosal barrier and reversing gut microbiota dysbiosis caused by sepsis. Specifically, pasteurized W. cibaria alleviates intestinal barrier damage and inflammation in SALI mice, enhancing the integrity of the intestinal mucosal barrier. Additionally, pasteurized W. cibaria increases the abundance of anti-inflammatory bacteria such as Muribaculaceae. Pasteurized W. cibaria also decreases the levels of LPS-producing bacteria, including Escherichia-Shigella and Helicobacter, leading to significant attenuation in metabolic endotoxemia, which in turn alleviates excessive lung inflammation in septic mice. Conclusions Pasteurized W. cibaria has the potential to act as a postbiotic agent, improving sepsis-induced gut microbiota dysbiosis and acute lung injury, and providing a novel strategy for treating SALI.